Penerapan Strategi Public Relations Melalui Penjualan Tiket Konser Dalam Menjaga Citra Tiket.Com Di Indonesia - Limarandani, Ni Putu; Alvitri, Zahra Aurelia; Hidayati, Ratih Kurnia; Mardiana, Dwi Kristi (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2024)
Public relations has an important role in a company. The existence of public relations helps companies to form a positive image in front of the public. Tiket.Com is an Online Travel Agent (OTA) themed company. Tiket.Com has an innovative product, namely TO DO tickets with a choice of rides, attractions, music concerts, tourist activities, and other travel needs. The spread of business competition with fellow OTA competitors is a challenge for Tiket.Com to improve a positive image. The purpose of this study is to analyze public relations strategies in maintaining the image of Tiket.com companies through ticket sales for music concerts in Indonesia. The method used is a qualitative method through interview, observation and documentation techniques using the concept of data analysis used by researchers is the Miles and Huberman model. The result of this study is Tiket.com is an online ticket booking platform that has a public relations division that is responsible for building the company's image through various activities.